Colon capsule endoscopy in colorectal cancer screening: a systematic review - Vuik, Fanny E. R.; Nieuwenburg, Stella A. V.; Moen, Sarah; Spada, Cristiano; Senore, Carlo; Hassan, Cesare; Pennazio, Marco; Rondonotti, Emanuele; Pecere, Silvia; Kuipers, Ernst J.; Spaander, Manon C. W. (Endoscopy, 2021)
Introduction Primary colonoscopy and fecal immunochemical test (FIT) are the most commonly used colorectal cancer (CRC) screening modalities. Colon capsule endoscopy (CCE) might be an alternative. Data on the performance of CCE as a CRC screening tool in a screening population remain scarce. This is the first systematic review to provide an overview of the applicability of CCE as a CRC screening tool.Methods A systematic search was conducted of literature published up to September 2020. Studies reporting on CRC screening by second-generation CCE in an average-risk screening population were included.Results 582 studies were identified and 13 were included, comprising 2485 patients. Eight studies used CCE as a filter test after a positive FIT result and five studies used CCE for primary screening. The polyp detection rate of CCE was 24 % – 74 %. For polyps > 6 mm, sensitivity of CCE was 79 % – 96 % and specificity was 66 % – 97 %. For polyps ≥ 10 mm, sensitivity of CCE was 84 % – 97 %, which was superior to computed tomographic colonography (CTC). The CRC detection rate for completed CCEs was 93 % (25/27). Bowel preparation was adequate in 70 % – 92 % of examinations, and completion rates varied from 57 % to 92 %, depending on the booster used. No CCE-related complications were described.Conclusion CCE appeared to be a safe and effective tool for the detection of CRC and polyps in a screening setting. Accuracy was comparable to colonoscopy and superior to CTC, making CCE a good alternative to colonoscopy in CRC screening programs, although completion rates require improvement.